2018
DOI: 10.1002/cncr.31635
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of breast cancer genetic risk assessment in a federally qualified health center

Abstract: Background The United States Preventive Services Task Force (USPSTF) endorses routine screening for genetic risk for breast/ovarian cancer as a component of primary healthcare. Implementation of this recommendation may prove challenging, especially in clinics serving disadvantaged communities. Methods We tested the feasibility of implementing the USPSTF mandate at a Federally Qualified Health Center (FQHC) in order to identify women eligible for genetic counseling (GC). A 12-month usual care phase was follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…The PAT has the highest sensitivity (100%), high specificity (93%) and is sensitive to BRCA1/2 risk (Hoskins et al, 2006; Hoskins et al, 2018;Teller et al, 2010). The instrument was tested on diverse race/ethnic groups and income levels (Hoskins et al, 2018); however, no study has examined its utility in Hispanic populations. The PAT point-scoring system assigns a certain value for each case of breast cancer within a family, accounting for both maternal and paternal lineages.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PAT has the highest sensitivity (100%), high specificity (93%) and is sensitive to BRCA1/2 risk (Hoskins et al, 2006; Hoskins et al, 2018;Teller et al, 2010). The instrument was tested on diverse race/ethnic groups and income levels (Hoskins et al, 2018); however, no study has examined its utility in Hispanic populations. The PAT point-scoring system assigns a certain value for each case of breast cancer within a family, accounting for both maternal and paternal lineages.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we test the Pedigree Assessment Tool (PAT), because it is one of the tools recommended for risk evaluation (Hoskins et al, 2018; Hoskins, Zwaagstra, & Ranz, 2006; Moyer, 2014) and because of its ease of use in both a community and clinic setting compared with other instruments like the Myriad II and Penn II (Teller et al, 2010). We make use of the El Paso and Hudspeth County Breast Cancer Education, Screening and NavigaTion program (BEST) data to assess the utility of the PAT in detecting the prevalence of HBC in our target population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides an opportunity to impact breast cancer disparities by identifying women with the highest risk so that enhanced screening and preventive measures can be initiated, including referral for GC and germline DNA testing of cancer susceptibility genes. Earlier work from our group showed that it is feasible to implement CGRA in federally qualified health centers (FQHC) in underserved minority communities, but uptake of counseling among high‐risk AA women who are referred for GC is very low 22 . Increasing the use of GC among AA women is a key step in developing a successful personalized medicine strategy for addressing breast cancer disparities that tailors screening and preventive care to individual level of risk.…”
Section: Introductionmentioning
confidence: 99%
“…19 Point-of-care educational support can be provided to patients at clinic visits before or during already-scheduled counseling or testing appointments, limiting barriers in teaching and allowing for assessment of understanding in real time. 20 the USPSTF guidelines have been in place for more than a decade, but PCPs need adequate tools to participate fully in preventive oncology.…”
mentioning
confidence: 99%